Numerical study of some high PM10 level episodes. (1st January 2011) - Todorova, Angelina; Gadzhev, Georgi; Jordanov, Georgi; Syrakov, Dimiter; Ganev, Kostadin; Miloshev, Nikolai; Prodanova, Maria
The study examines the ability of US EPA Models-3 system to reproduce air pollution episodes and to evaluate the role of different processes in the PM10 pattern formation. The case study focuses on three major PM10 episodes, that occurred over Germany in February and March of 2003. The emission input is prepared on the basis of the TNO inventory. The simulated PM10 concentrations are compared with measurements from the EMEP stations in Germany. The Integrated Process Rate Analysis function of CMAQ is applied for clarifying the role of different processes in forming PM10 concentration peaks.